Pelatihan Penggunaan ChatGPT berbasis Kerangka Literasi AI untuk Meningkatkan Integritas Akademik Mahasiswa - Syairofi, Ahmad (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
Although ChatGPT can provide rapid feedback and lead to a transformation of teaching and learning, its use raises pressing ethical dilemmas for its users. To overcome this issue, the AI literacy of users needs to be increased to face educational challenges due to the use of this technology in the field of education. Therefore, this service aims to increase awareness of AI literacy and students' academic integrity in utilizing this technology. Adopting an AI Literacy Framework from an empirical study, an instructional design was developed to help students understand the advantages and disadvantages of ChatGPT, use ChatGPT for educational purposes, create commands appropriate to learning objectives, evaluate the material produced by the tool, and learn the ethics of using the information generated. This service program was based on community development using the ADDIE (Analysis, Design, Develop, Implement, Evaluate) method in the training process and was attended by 10 students from the English Education Study Program at the University of Al-Falah As-Sunniyah Kencong Jember. Through the application of the instructional design, students were facilitated to enhance their AI literacy awareness while increasing their academic integrity. AI literacy awareness has an important role in improving the quality of academic integrity in the era of AI technology.